2012
DOI: 10.3390/molecules18010074
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acidic Ionic Liquid Accelerated Halogenation of Organic Compounds with N-Halosuccinimides (NXS)

Abstract: The Brønsted-acidic ionic liquid 1-methyl-3-(4-sulfobutyl)imidazolium triflate [BMIM(SO3H)][OTf] was demonstrated to act efficiently as solvent and catalyst for the halogenation of activated organic compounds with N-halosuccinimides (NXS) under mild conditions with short reaction times. Methyl aryl ketones were converted into α-halo and α,α-dihaloketones, depending on the quantity of NXS used. Ketones with activated aromatic rings were selectively halogenated, however in some cases mixtures of α-halogenated ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 106 publications
0
14
0
Order By: Relevance
“…Health problems associated with IPV are often treated as problems in their own right rather than as the result of IPV [20,21]. Consequently, when the abuse remains undetected, the women may experience a secondary victimisation and the suffering of care [22,23]. Results from studies have shown that healthcare staff often lack relevant knowledge, are uncertain about how to ask, are concerned about breaching the woman's integrity, or are unsure about which intervention should be implemented once IPV is confirmed [18,24-27].…”
Section: Introductionmentioning
confidence: 99%
“…Health problems associated with IPV are often treated as problems in their own right rather than as the result of IPV [20,21]. Consequently, when the abuse remains undetected, the women may experience a secondary victimisation and the suffering of care [22,23]. Results from studies have shown that healthcare staff often lack relevant knowledge, are uncertain about how to ask, are concerned about breaching the woman's integrity, or are unsure about which intervention should be implemented once IPV is confirmed [18,24-27].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, apoptosis is induced via two main routes involving either the mitochondria or the activation of death receptors. The mitochondrial pathway is activated by a wide range of signals and involves the release of proteins (including cytochrome c) from the mitochondrial membrane space [28,29,35,36]. Our results indicated that the expression of cytochrome c and the activity of cleaved caspase-3 were greatly increased after rapamycin treatment in the presence of HGF, which suggested that the apoptosis was induced by engaging mitochondrial pathway, and catalytic activation of the caspases [29].…”
Section: Resultsmentioning
confidence: 85%
“…In the past few years, a new strategy was proposed to remove the residual LECs by inducing apoptosis [16]. Previous studies have shown that over expression of Bax or procaspase-3 is capable of inducing therapeutic programmed cell death of residual LECs in vitro and in vivo and preventing PCO in a rabbit model [28,29]. Recent studies have concentrated on the cytokines involved in the development of PCO that were produced by the LECs themselves and believed to play an important role [3,30,31,32,33,34].…”
Section: Resultsmentioning
confidence: 99%
“…In our continuous pursuit of sustainable synthetic protocols [ 33 , 34 , 35 , 36 , 37 ], including those where NXSs are used as reagents [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], we now report and introduce the use of substoichiometric amounts of these compounds as mediators for efficient and selective comprehensive metal-free direct esterification of carboxyl functionality in organic molecules under neat reaction conditions ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%